2019
DOI: 10.3389/fpsyg.2019.00376
|View full text |Cite
|
Sign up to set email alerts
|

Novel ERP Evidence for Processing Differences Between Negative and Positive Polarity Items in German

Abstract: One unresolved question about polarity sensitivity in theoretical linguistics concerns whether and to what extent negative and positive polarity items are parallel. Using event-related brain potentials (ERPs), previous studies found N400 and/or P600 components for negative and positive polarity violations with inconsistent results. We report on an ERP study of German polarity items. Both negative and positive polarity violations elicited biphasic N400/P600 effects relative to correct polarity conditions. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…Furthermore, we found an interaction between the licensing status and the contrast between NPIs and PPIs ( = 0.53, CrI = [0.08, 0.98], P(β > 0) = 0.99) 9 : In licensed conditions, there was no evidence for a difference in the naturalness of the tested NPIs and PPIs ( = 0.07, CrI = [-0.20, 0.37], P(β > 0) = 0.69), whereas in unlicensed conditions, the model indicated that PPIs were given higher naturalness ratings than NPIs ( = 0.61, CrI = [0.26, 0.95], P(β > 0) = 1). This is in line with theoretical and experimental work (Liu and Iordǎchioaia, 2018 ; Liu et al 2019 ) that argues that NPI violations and PPI violations are qualitatively distinct, such that NPI violations result in irrescuable ungrammaticality, whereas PPIs in negative contexts can often be saved (see also Introduction). Further comparisons between the tested PSIs demonstrated that both the NPI so recht (‘really’) and the PPI absolut (‘absolutely’) received somewhat higher naturalness ratings in non-licensing contexts than their counterparts jemals (‘ever’) ( = − 1.33, CrI = [− 1.81, − 0.87], P(β < 0) = 1) and durchaus (‘quite’) ( = − 0.88, CrI = [− 1.29, − 0.46], P(β < 0) = 1).…”
Section: The Current Studysupporting
confidence: 86%
See 1 more Smart Citation
“…Furthermore, we found an interaction between the licensing status and the contrast between NPIs and PPIs ( = 0.53, CrI = [0.08, 0.98], P(β > 0) = 0.99) 9 : In licensed conditions, there was no evidence for a difference in the naturalness of the tested NPIs and PPIs ( = 0.07, CrI = [-0.20, 0.37], P(β > 0) = 0.69), whereas in unlicensed conditions, the model indicated that PPIs were given higher naturalness ratings than NPIs ( = 0.61, CrI = [0.26, 0.95], P(β > 0) = 1). This is in line with theoretical and experimental work (Liu and Iordǎchioaia, 2018 ; Liu et al 2019 ) that argues that NPI violations and PPI violations are qualitatively distinct, such that NPI violations result in irrescuable ungrammaticality, whereas PPIs in negative contexts can often be saved (see also Introduction). Further comparisons between the tested PSIs demonstrated that both the NPI so recht (‘really’) and the PPI absolut (‘absolutely’) received somewhat higher naturalness ratings in non-licensing contexts than their counterparts jemals (‘ever’) ( = − 1.33, CrI = [− 1.81, − 0.87], P(β < 0) = 1) and durchaus (‘quite’) ( = − 0.88, CrI = [− 1.29, − 0.46], P(β < 0) = 1).…”
Section: The Current Studysupporting
confidence: 86%
“…We distinguish between negative polarity items (NPIs) like ever, which require a negative context to be licensed (1a), and positive polarity items (PPIs) like Finally, the distribution of PPIs is further complicated by the fact that they can be rescued (Szabolcsi 2004) if the negation scoping over the PPI is itself outscoped by an (at least) downward-entailing operator (7), or if the negation is understood as an emphatic denial or contrast to an earlier assertion (8). By comparison, unlicensed NPIs always make the sentence ungrammatical; NPI and PPI violations are thus qualitatively distinct (Liu and Iordǎchioaia 2018; see also Liu et al 2019 for experimental evidence).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the methods used here might be problematic. First, some of the fillers involve unlicensed polarity items, e.g., jemals ‘ever’ in positive sentences, which are ungrammatical (see Ladusaw, 1980 ; Giannakidou, 2011 ; Liu et al, 2019 ). This might have contributed to the ceiling effect for the wenn/falls sentences.…”
Section: Methodsmentioning
confidence: 99%
“…Their study investigates the question how polarity items are acquired by looking at 11- to 12-year-olds’ comprehension of German NPIs and PPIs. PPIs and NPIs are restricted in their distribution to contexts of the appropriate polarity (Liu et al, 2019 ), but the complexity in the exact characteristics that render particular contexts (anti-)licensing and the considerable variability in individual polarity items’ sensitivity to such contexts poses a challenge to language learners. Previous research based on sentence production data (Lin et al, 2015 , 2018 ; O’Leary & Crain, 1994 ; Tieu, 2013 ; Tieu & Lidz, 2016 ) suggest that children show an early sensitivity to the limited distribution of polarity items, although their knowledge of the set of licensing expressions grows more sophisticated with time.…”
Section: Research Topics At Focusmentioning
confidence: 99%